2023
DOI: 10.1186/s12885-023-10703-x
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram based on platelet-to-lymphocyte ratio for predicting pathological complete response of breast cancer after neoadjuvant chemotherapy

Abstract: Objective To investigate the role of platelet-to-lymphocyte ratio (PLR) in complete pathological response (pCR) of breast cancer (BC) patients after neoadjuvant chemotherapy (NAC), as well as to establish and validate a nomogram for predicting pCR. Methods BC patients diagnosed and treated in the First Affiliated Hospital of Xi’an Jiaotong University from January 2019 to June 2022 were included. The correlation between pCR and clinicopathological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…A total of seven studies investigated the WCC or its individual components ( Tables S3–S6 ) 19 , 23 , 24 , 32 , 33 , 36 , 50 ; one study included only patients with HER2+ breast cancer 19 , whereas the others included all subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of seven studies investigated the WCC or its individual components ( Tables S3–S6 ) 19 , 23 , 24 , 32 , 33 , 36 , 50 ; one study included only patients with HER2+ breast cancer 19 , whereas the others included all subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…A total of three studies 19 , 23 , 33 were eligible for meta-analysis of the association between the WCC (using a cut-off value of between 6.13 × 10 9 /l and 8.66 × 10 9 /l) and a pCR. The meta-analysis suggested that patients with a low pretreatment WCC were more likely to achieve a pCR (OR 1.96 (95% c.i.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaytaz Tekyol et al found that PLR value was associated with chemotherapy sensitivity and could serve as a predictive marker of the therapeutic effect of NACT in BC 34. Similarly, Jarroudi et al showed that PLR was associated with OS and DFS in BC treated with NACT 43 74. However, some other studies reported that the PLR value has no significant predictive effect on pCR rate, DFS or OS in BC treated with NACT 25 48.…”
Section: Discussionmentioning
confidence: 99%